2019
DOI: 10.2116/analsci.19p069
|View full text |Cite
|
Sign up to set email alerts
|

Application of NOBIAS Chelate-PA 1 Resin to the Determination of Zirconium, Niobium, Hafnium, and Tantalum in Seawater

Abstract: Zirconium, niobium, hafnium, and tantalum are dissolved in seawater as hydroxide complexes at a concentration as low as 0.01-370 pmol kg-1 and are expected to be potential tracers for water masses in the ocean. Herein, we report a new analytical method for the multielemental determination of the four elements on the basis of column extraction, using a NOBIAS Chelate-PA 1 resin that contains ethylenediaminetriacetic acid groups. The elements were collected on the resin from seawater that had been added with 3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
8
13
0
Order By: Relevance
“…For example, seawater and surface soils with predominant global fallout have 90 Sr/ 90 Zr atomic ratios of $10 À11 . 1,13,16 Therefore, chemical separation and mass spectrometry combined should ideally be capable of separating 90 Zr by a factor >10 12 . Previous studies have reported LODs of <1 Bq (1 Bq z 1.3 Â 10 6 atoms) by ICP-MS/MS, 8,9 4 mBq by RIMS, 11 and <1 mBq by TIMS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, seawater and surface soils with predominant global fallout have 90 Sr/ 90 Zr atomic ratios of $10 À11 . 1,13,16 Therefore, chemical separation and mass spectrometry combined should ideally be capable of separating 90 Zr by a factor >10 12 . Previous studies have reported LODs of <1 Bq (1 Bq z 1.3 Â 10 6 atoms) by ICP-MS/MS, 8,9 4 mBq by RIMS, 11 and <1 mBq by TIMS.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the efficiency of separation, it is desirable to develop effective separation resins for Pu(IV), as well as other resins for metal ions. [8][9][10][11][12] Microbial metabolite desferrioxamine B (DFB), a trihydroxamate-based siderophore produced by the actinobacteria Streptomyces pilosus, has a very strong chelating ability for many high-valence ions under certain conditions. [13][14][15] For instance, it has been reported that DFB chelates with Pu(IV), 13,14 Am(III), 16 Cm(III), 17 and U(VI) 15 in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…As these elements are not stable in solution without HF, their determination is easily affected by storage conditions and the choice of analytical methods. Table 1 summarizes the concentrations of dZr, dNb, dHf, and dTa in the open ocean reported previously (Firdaus et al, 2011;Firdaus et al, 2008;Firdaus et al, 2018;Godfrey et al, 1996;Godfrey et al, 2009;McKelvey and Orians, 1993;McKelvey and Orians, 1998;Poehle and Koschinsky, 2017;Rahlf et al, 2021;Rickli et al, 2009;Rickli et al, 2014;Sohrin et al, 1998;Stichel et al, 2012;Sun and Li, 2015;Tanaka et al, 2019). The concentrations of the four elements in seawater are extremely low: 7 -380 pmol/kg for dZr, 0.9 -30 pmol/kg for dNb, 0.06 -3.9 pmol/kg for dHf, and 0.002 -7.2 pmol/kg for dTa.…”
Section: Introductionmentioning
confidence: 88%
“…The preconcentration methods using column extraction with a chelating resin have been reported for the determination of Zr, Nb, Hf, and Ta in seawater. To date we have developed preconcentration methods of the four elements using 8-hydroxyquinoline chelating resin (TSK-8HQ) (Firdaus et al, 2007) and NOBIAS Chelate-PA 1 resin with ethylenediaminetriacetic acid and iminodiacetic acid groups (Tanaka et al, 2019). The vertical profiles of dZr, dNb, dHf, and dTa in the North Pacific were investigated using these methods (Firdaus et al, 2011;Tanaka et al, 2019).…”
Section: Introductionmentioning
confidence: 99%